(untitled) (Journal of Contemporary Educational Policies and Practices, 2020)
Currently, the research and teaching work at the university is one of the top concerns. For those who teach Political economics of Marxism and Leninism, in addition to equipping with political theory, lecturers must attach to reality, stick to the practical situation so that learners understand and firmly grasp the theory. To promote the process of research and teaching this subject artificial intelligence tools were born. Artificial intelligence (AI) is coming to life strongly, replacing many manual and labor-intensive jobs. The subject of Political economics of Marxism and Leninism is a difficult and abstract subject, so how to shorten the time to study this document and process this large amount of information? This article aims to address the difficulties faced by teachers when conducting the process of finding data, thereby making findings and assessment on a number of tools to support teachers in finding information. From the results of the analysis and selection, we have selected 4 AI softwares with outstanding advantages with support for teachers. From there, recommendations to enhance and develop the features of AI tools for the study and teaching of Political economics of Marxism and Leninism subjects in Vietnam are made.